Guarding dogs as a mitigation tool in human-wildlife conflict - case study: the Anatolian Shepherd Dog breeding project in Namaqua National Park - Binge, Elizabeth Naudé (Department of Environmental and Geographical Science, 2017)
This study conducted an evaluation of farmer and shepherd perceptions on Anatolian Shepherd dogs, used as livestock guarding dogs to mitigate farmer–wildlife conflict and meet conservation ends. The case study involved Anatolian Shepherd dogs bred at the Anatolian Shepherd Dog Breeding Project in the Namaqua National Park, and placed mostly on farms and at stock posts near the Namaqua National Park in the Northern Cape. The data were collected during structured and semi-structured interviews with livestock farmers and shepherds that received Anatolian Shepherd dogs from the Breeding Project. Anatolian Shepherd dogs were evaluated in terms of their contribution to reduce livestock losses and conservation of wildlife species. In terms of effectiveness in preventing or reducing livestock losses, 84% of the dogs eliminated or reduced livestock losses. Respondent satisfaction with the dogs was high, with 95% of respondents willing to recommend the Breeding Project and the use of Anatolian Shepherd dogs. Of the respondents, 95% perceived their dogs to be economically beneficial. Another 48% of respondents reported some form of behavioural problems at least once during the placement of the dogs. The most common reported problem was resting in the shade rather than accompanying the livestock. However, corrective training was effective in all cases where training was undertaken immediately. In terms of conservation, fewer respondents used lethal predator control methods in the years after placement of the dogs than before their placement. The overall perception regarding the use of lethal control methods (e.g. gin traps, shooting and poison) was that such control is cruel and that it is better to use non-lethal control methods only. However, a few respondents reported that lethal control measures were occasionally necessary to make a living when no other control measures were available, especially when the herd was relatively large. The effects of Anatolian Shepherd dogs on non-predator species in this study were minimal. The presence of the dogs therefore aided predator conservation and improved farmer tolerance of predators, especially by effectively reducing livestock losses.